Perioperative oxygen administration in patients undergoing major non-cardiac surgery under general anaesthesia in Australia and New Zealand. Issue 3 (May 2023) - Frei, Daniel R; Beasley, Richard; Campbell, Douglas; Leslie, Kate; Merry, Alan; Moore, Matthew; Myles, Paul S; Ruawai-Hamilton, Laura; Short, Timothy G; Sibanda, Nokuthaba; Young, Paul J
The practice of anaesthetists relating to the administration of intraoperative oxygen has not been previously quantified in Australia and New Zealand. The optimal regimen of intraoperative oxygen administration to patients undergoing surgery under general anaesthesia is not known, and international recommendations for oxygen therapy are contradictory; the World Health Organization (WHO) recommend administering an intraoperative fraction of inspired oxygen of at least 0.8, while the World Federation of Societies of Anaesthesiologists, British Thoracic Society, and Thoracic Society of Australia and New Zealand recommend a more restrictive approach. We conducted a prospective observational study to describe the pattern of intraoperative oxygen administration among anaesthetists in Australia and New Zealand and, second, to determine the proportion of anaesthetists who administer intraoperative inspired oxygen in accordance with the WHO recommendations. We identified 150 anaesthetists from ten metropolitan hospitals in Australia and New Zealand and observed the patterns of intraoperative oxygen administration to American Society of Anesthesiologists physical status classification (ASA) 3 or 4 patients undergoing prolonged surgery under general anaesthesia. The median (interquartile range) intraoperative time-weighted mean fraction of inspired oxygen (FiO2 ) for all participants in the study was 0.47 (0.40–0.55). Three out of 150 anaesthetists (2%, 95% confidence interval 0.4 to 5.7) administered an average intraoperative FiO2 of at least 0.8. These findings indicate that most anaesthetists routinely administer an intermediate level of oxygen for ASA 3 or 4 adult patients undergoing prolonged surgery in Australia and New Zealand, rather than down-titrating inspired oxygen to a target pulse oximetry reading (SpO2 ) or administering liberal perioperative oxygen therapy in line with the current WHO recommendation.